Executive Characteristics: The Effect of Accounting Conservatism, Financial Distress, Transfer Pricing on Tax Avoidance - Honorris, Prasetyo; Trisnawati, Estralita; Sriwati, Sriwati (E-Jurnal Akuntansi; Vol 35 No 1 (2025)DO - 10.24843/EJA.2025.v35.i01.p05, 2025)
This study examines the moderating role of executive characteristics in the relationship between accounting conservatism, financial distress, transfer pricing, and tax avoidance. The research utilizes secondary data obtained from the financial statements of companies operating in the Basic Industry and Chemical manufacturing sectors listed on the Indonesia Stock Exchange from 2019 to 2023. The analysis is conducted using moderated regression analysis. The findings indicate that accounting conservatism and transfer pricing do not have a significant effect on tax avoidance, whereas financial distress exhibits a negative relationship with tax avoidance. Furthermore, executive characteristics do not moderate the relationship between accounting conservatism or transfer pricing and tax avoidance. However, executive characteristics positively moderate the relationship between financial distress and tax avoidance. Keywords: Tax Avoidance; Conservatisme Accounting; Financial Distress; Transfer Pricing, Executive Characteristics.